Numerical simulation on gas production from methane hydrate sediment by depressurization in a reactor with ice formation. (1st December 2020) - Shao, Yazhou; Yang, Longbin; Zhang, Qun; Wang, Shidong; Wang, Kunfang; Xu, Runzhang
Highlights: Lower initial pressure leads to lower gas production rate. Ice formation influences the gas production rate. An optimal well pressure exists by balancing driving force and ice inhibition. Abstract: Natural gas hydrate as a potential backup energy has very important scientific and social values. This paper aims at analyzing the gas production characteristic of methane hydrate sediment via depressurization. The physical model of 1 L cylindrical reactor is established and numerically simulated with the hydrate calculation software TOUGH + HYDRATE_v1.5. Based on the experiments, the cases in which ice formation are set to different initial reservoir pressures (2.0 MPa, 2.5 MPa, 3.0 MPa and 4.0 MPa) for numerical simulation to see the dissociation characteristics and heat and mass transfer during hydrate dissociation. The simulation results indicate that under the same driving force, the rate of hydrate dissociation increases with the initial pressure and the cumulative volumes of gas produced of the well and the sediment is the same due to the same initial hydrate saturation. The heat and mass transfer affected by ice formation plays an important role in hydrate dissociation and the temperature distribution in the sediment. When there is ice formation inside the sediment which inhibits the heat and mass transfer inside the sediment, the driving force should be carefully selected for different initial pressures to reduce the inhibitory effect of ice formation on hydrate dissociation.